2021
DOI: 10.3233/shti210317
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Remote Learning in Nursing Education During the COVID-19 Pandemic

Abstract: Due to the corona (COVID-19) pandemic, several countries are currently conducting non-face-to-face education. Therefore, teachers of nursing colleges have been carrying out emergency remote education. This study developed a questionnaire to understand the status of Emergency Remote Learning (ERL) in nursing education internationally, translated it into 7 languages, and distributed it to 18 countries. A total of 328 nursing educators responded, and the most often used online methods were Social networking techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The negative effects of the pandemic on people from all walks of life are known to affect all of their activities in their everyday lives. At the beginning of this period of sudden transition from traditional face-to-face education to virtual platform, nursing education was continued with the known teaching techniques, and this entered the literature as the concept of emergency remote education 25 . However, as the pandemic was prolonged, the lessons continued with online distance education, and as a result, students had to spend increasingly more time online, and thus, the concept of Zoom fatigue began to be investigated 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effects of the pandemic on people from all walks of life are known to affect all of their activities in their everyday lives. At the beginning of this period of sudden transition from traditional face-to-face education to virtual platform, nursing education was continued with the known teaching techniques, and this entered the literature as the concept of emergency remote education 25 . However, as the pandemic was prolonged, the lessons continued with online distance education, and as a result, students had to spend increasingly more time online, and thus, the concept of Zoom fatigue began to be investigated 26 .…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of this period of sudden transition from traditional face-to-face education to virtual platform, nursing education was continued with the known teaching techniques, and this entered the literature as the concept of emergency remote education. 25 However, as the pandemic was prolonged, the lessons continued with online distance education, and as a result, students had to spend increasingly more time online, and thus, the concept of Zoom fatigue began to be investigated. 26 A study conducted with nursing students demonstrated that Zoom fatigue was real and may have adverse consequences on nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Such education will bring innovation that expands and evolves not only in the school context but also in daily life [ 7 , 8 ]. Schools were closed owing to the onset of COVID-19, with non-face-to-face practice or distance education replacing video learning or simulation classes in the nursing education clinical practicum [ 9 ], leading to a greater interest in VE simulation education.…”
Section: Introductionmentioning
confidence: 99%
“…Learners’ immersion affects satisfaction and perception, even in VE education contexts [ 39 ]. Although several studies have been conducted on satisfaction evaluation for simulation-based learning [ 6 , 7 , 9 , 20 , 26 , 33 , 40 , 41 ], there is a lack of research on the satisfaction dimesion related to VE education. Consequently, there is limited information to support designing and applying VE educational content for instructors unfamiliar with the use of VE simulations.…”
Section: Introductionmentioning
confidence: 99%
“…According to the simulation framework, the ve key components of simulation are participant, facilitator, educational practices, simulation design characteristics, and outcomes [23]. The instructional design indicates the extent to which learners perceive the learning objectives, planning, delity, complexity, cues, and debrie ng [24,25]. Outcomes include knowledge, skill performance, learner satisfaction, critical thinking, and self-con dence [23].…”
Section: Introductionmentioning
confidence: 99%